Retrieving a world of fiction: building an index – and an archive – of serialized novels in Australian newspapers, 1850–1914. (June 2015) - Bode, Katherine; Hetherington, Carol
Abstract : The authors explain how the vagaries of fiction publishing in Antipodean newspapers in the nineteenth and early twentieth century have shaped a digital project to create an index and archive of the fiction.